Public awareness of side effects of systemic steroids in Asir region, Saudi Arabia - Nouf Ahmed Alhammadi; Saud Mushabbab Mohammed Al Oudhah; Mofareh Ahmed Mofareh Asiri; Mohammed Abdullah Alshehri; Bassam Ahmed B. Almutairi; Abdullah Mohammed Abdullah Thalibah; Fahad Nasser Mohammed Asiri; Abdullah Saad Aldarani Alshahrani (Journal of Family Medicine and Primary Care, 2023)
Background: Corticosteroids have been used since the 50s and it represent the most important and frequently used class of anti-inflammatory and immunosuppressive drugs for the treatment of several diseases such as numerous neoplastic, asthma, allergy, rheumatoid arthritis, and dermatological disorders. This study aims to determine the public awareness of side effects of systemic steroids in Asir region, Saudi Arabia. Methods: A descriptive cross-sectional web-based study was used. An online questionnaire was developed by the study researchers based on the literature review and consultations of the field experts. The questionnaire included the following components: Participants demographic data, medical history, and steroids use. Also, it covered participants awareness regarding systemic steroids and side effects. Results: A total of 439 participants fulfilling the inclusion criteria completed the study questionnaire. Ages ranged from 18 to 65 years with mean age of 26.1 ± 13.9 years old, of those, 227 (51.7%) respondents were males. Around 346 (78.8%) had poor overall awareness level while only 93 (21.2%) had good awareness regarding systematic steroids. The study also showed that awareness was significantly higher among young aged participants in the health care field and among those who previously used steroids. Two hundred and eighty two (64.2%) of the respondents reported previous use of steroids. Conclusion: In conclusion, the current study showed that nearly one out of each five people know about systemic steroids and related side effects which is below the satisfactory level. Higher awareness was observed with regards drug associated side effects and long-term use consequences.